First clonal spread of KPC-producing Pseudomonas aeruginosa in Buenos Aires, Argentina - Santella, Gisela (2012)
Fil: Santella, Gisela. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina